Effects of Various High a-Olefins on the Terpolymerization with Metallocene Catalyst and Cocatalyst System - Kim1, T.W.; Cho2, U.R.; Kim1, D.H. (Asian Journal of Chemistry, 2013)
Terpolymers composed of ethylene, high a-olefin and p-methyl styrene using a rac-Et(Ind)2ZrCl2 catalyst and cocatalyst system were synthesized. The terpolymers obtained were characterized by 1H NMR and 13C NMR spectroscopy. The catalytic activity, molecular weight, molecular weight distribution and compositions of the polymers were analyzed. The thermal properties of the polymers were investigated. The crystallinity of the terpolymers was determined by differential scanning calorimetry and wide-angle X-ray scattering. The catalytic activity increased to some degree with increasing chain length of the high a-olefin in the terpolymers. The crystallinity, mechanical and thermal properties decreased with increasing chain length of high a-olefins in the terpolymers.